NDUFAF6-Related Leigh Syndrome Caused by Rare Pathogenic Variants: A Case Report and the Focused Review of Literature - Kim, Jaewon; Lee, Jaewoong; Jang, Dae-Hyun (Frontiers in Pediatrics, 2022)
Leigh syndrome is a neurodegenerative disorder that presents with fluctuation and stepwise deterioration, such as neurodevelopmental delay and regression, dysarthria, dysphagia, hypotonia, dystonia, tremor, spasticity, epilepsy, and respiratory problems. The syndrome characteristically presents symmetric necrotizing lesions in the basal ganglia, brainstem, cerebellum, thalamus, and spinal cord on cranial magnetic resonance imaging. To date, more than 85 genes are known to be associated with Leigh syndrome. Here, we present a rare case of a child who developed Leigh syndrome due to pathogenic variants of NDUFAF6, which encodes an assembly factor of complex I, a respiratory chain subunit. A targeted next-generation sequencing analysis related to mitochondrial disease revealed a missense variant (NM_152416.4:c.371T>C; p.Ile124Thr) and a frameshift variant (NM_152416.4:c.233_242del; p.Leu78GInfs*10) inherited biparentally. The proband underwent physical therapy and nutrient cocktail therapy, but his physical impairment gradually worsened